Enhancing Scientific Literacy Through Guided Discovery with SELWAN Application in Science Learning - Sulaihah*, Sulaihah; Mulia, Mala; Widodo, Wahono; Sukarmin, Sukarmin; Dalee, Abdullah D (Universitas Syiah Kuala, 2024)
Scientific literacy is one of the crucial skills in digitalization era. Scientific literacy is one of parameters in International Student Assessment Program (PISA). Indonesia was still far from the average PISA assessment. Pupils' scientific literacy abilities are now judged to be at a poor level. The major goal of this study is to know the effectiveness of using the guided discovery with the SELWAN app in improving pupils' scientific literacy. This research used a non-equivalent control group design and was a quasi-experiment. During the school year 2022-2023, this inquiry was carried out at Nazhatut Thullab Middle School. All seventh-grade pupils from Nazhatut Thullab Middle School are included in the study. The experimental group consists of 25 pupils from class VII E, and the control group consists of 23 pupils from class VII F. For data analysis, the independent sample t-test is used to examine pupils' scientific literacy abilities. The findings show that deploying the guided discovery in conjunction with the SELWAN application has a detectable influence on pupils' scientific literacy. The SELWAN app's guided discovery learning received a resoundingly favorable reaction from pupils, with 81.06% falling into the ideal category